2004
DOI: 10.1016/j.jacc.2004.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic and electroanatomic changes in the human atrium associated with age

Abstract: Aging is associated with regional conduction slowing, anatomically determined conduction delay at the crista, and structural changes that include areas of low voltage. In addition, impairment of sinus node function and an increase in atrial ERP occurred with aging. This electrical and structural remodeling may explain the increased propensity to AF with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
270
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 385 publications
(296 citation statements)
references
References 31 publications
(38 reference statements)
21
270
0
2
Order By: Relevance
“…11 Finally, given the greater incidence of AF in older patients, the group tested the hypothesis that right atrial voltage would be lower in older patients by studying 13 patients ≥60 years old, 13 patients between 31 and 59 years old, and 13 patients ≤30 years old: once again, they found lower right atrial voltage and greater heterogeneity in their study group (the older patients). 13 Corradi et al found a greater amount of interstitial fibrosis in the posterior wall compared to the left atrial appendage in AF patients undergoing mitral valve surgery. 6 Our findings suggest that the regional differences may be exaggerated in AF patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…11 Finally, given the greater incidence of AF in older patients, the group tested the hypothesis that right atrial voltage would be lower in older patients by studying 13 patients ≥60 years old, 13 patients between 31 and 59 years old, and 13 patients ≤30 years old: once again, they found lower right atrial voltage and greater heterogeneity in their study group (the older patients). 13 Corradi et al found a greater amount of interstitial fibrosis in the posterior wall compared to the left atrial appendage in AF patients undergoing mitral valve surgery. 6 Our findings suggest that the regional differences may be exaggerated in AF patients.…”
Section: Discussionmentioning
confidence: 96%
“…9 Low voltage detected by CARTO accurately correlates with areas of fibrosis, 10 and studies examining voltage in the right atrium have demonstrated lower voltage in patients with sinus node disease, 11 congestive heart failure, 12 and advancing age. 13 Previous studies involving left atrial anatomic maps of AF patients have explored the value of targeting complex and high-frequency activity during AF 7, 14 and the prognostic significance of large areas of scarring in AF patients, 15 but none have examined sinus rhythm maps to characterize regional voltage.…”
Section: Introductionmentioning
confidence: 99%
“…14,587,1098,1099 The results of a subset of these studies suggest that AF can be viewed, in some patients, as a rate-related atrial cardiomyopathy. As discussed elsewhere in the document, AF can also follow and be the consequence of prior atrial damage and fibrosis (atrial myopathy).…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…165,166 Clinical mapping studies have also demonstrated similar findings of conduction abnormalities, prolonged refractoriness, reduced myocardial voltage, and a greater number of double potentials and fractionated electrograms. 167,168 Perhaps as a result of these atrial changes, alteration of wavefront propagation velocities has been described with an inverse correlation to age. 169 Histologically, fibrotic changes are the most obvious alteration (EHRAS Class II; see Table 2).…”
Section: Ageingmentioning
confidence: 99%
“…167 It has been a powerful research tool that has enhanced our understanding of the atrial substrate in patients with paroxysmal and persistent atrial fibrillation and 74,434 those who have failed initial PV antrum isolation. 435 Unlike cardiac MR, CT, or echocardiography, EAM requires invasive catheterization and mapping.…”
Section: Imaging With Electroanatomic Mappingmentioning
confidence: 99%